Gender, Health and Healing: Perceptions and Experiences from Women Survivors Affected by Tuberculosis in Kashmir. - Akhter, Rubeena; Bhat, Yasir Hamid (International Journal of Psychosocial Rehabilitation, 2026)
The concept of right to health as a human right has emerged as a result of growing consciousness about the dignity of human life all over the world. Healthcare is undoubtedly considered as a socio-medical concept, and not just a medical one, therefore, it doesn’t mean that mere medical treatment during illness is an achievement or progress. Since women constitute nearly half of the world’s population and they have also an additional responsibility of reproduction and motherhood, therefore, they must be given equal status in accessing health care services and should be adequately informed about a particular disease or illness. Gender for women has been a powerful indicator of inequality and discrimination, which influences not only their state of health and wellbeing but also their ability to seek care. Same is true for Tuberculosis which has been plaguing humankind since time immemorial. Women are often affected differently by Tuberculosis than men. Growing evidence suggests that Tuberculosis has implications for women’s reproductive health, including links with infertility, risks of prematurity, obstetric morbidity, and low birth weight. The present paper is an attempt to sketch a picture of women’s suffering from Tuberculosis in Kashmir. It also tries to document their perceptions and lived experiences of being Tuberculosis survivors.